Respuesta :
Answer:
Step-by-step explanation:
ax^2+bx+c
-b +- sqaure root of b^2 -4ac/2a
-2 +- square root (2)^2-4(2)(-1)/2(2)
-2 +- square root 4+8 /4
-2 +- 2 square root 3 /4
reduce
-1 +- square root 3/2
Answer:
[tex]\large\boxed{x=\dfrac{-1-\sqrt3}{2}\ or\ x=\dfrac{-1+\sqrt3}{2}}[/tex]
Step-by-step explanation:
The quadratic formula of a quadratic equation:
[tex]ax^2+bx+c=0[/tex]
Discriminant of a Quadratic is [tex]\Delta=b^2-4ac[/tex]
If Δ < 0, then an equation has no real solution (has two complex solutions)
If Δ = 0, then an equation has one real solution [tex]x=\dfrac{-b}{2a}[/tex]
If Δ >0, then an equation has two real solutions [tex]x=\dfrac{-b\pm\sqrt{\Delta}}{2a}[/tex]
==========================================
We have the equation:
[tex]2x^2+2x-1=0\\\\a=2,\ b=2,\ c=-1[/tex]
Substitute:
[tex]\Delta=2^2-4(2)(-1)=4+8=12>0\\\\\sqrt\Delta=\sqrt{12}=\sqrt{4\cdot3}=\sqrt4\cdot\sqrt3=2\sqrt3[/tex]
[tex]x=\dfrac{-2\pm2\sqrt3}{(2)(2)}=\dfrac{-2\pm2\sqrt3}{4}[/tex] simplify by 2
[tex]x=\dfrac{-1\pm\sqrt3}{2}[/tex]